2018
DOI: 10.1158/1055-9965.epi-18-0175
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Global DNA Methylation, and Breast Cancer Risk: A Systematic Literature Review and Meta-analysis

Abstract: The extent to which physical activity reduces breast cancer risk through changes in global DNA methylation is unknown. We systematically identified studies that investigated the association between: (i) physical activity and global DNA methylation; or (ii) global DNA methylation and breast cancer risk. Associations were quantified using random-effects models. Heterogeneity was investigated through subgroup analyses and the -test and statistics. Twenty-four studies were reviewed. We observed a trend between hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 65 publications
1
33
0
Order By: Relevance
“…Physical activity decreases the duration and intensity of fatigue [ 8 , 9 ], reduces anxiety and depression [ 10 ], increases muscle mass and strength, decreases disability in the upper extremities [ 11 ] and improves quality of life [ 12 , 13 ], as well as restoring and even improving functionality and well-being in women who have overcome breast cancer [ 14 ]. Several meta-analyses and reviews affirm that physical activity also contributes to reducing the risk of breast cancer recurrence [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], while others have obtained neutral results, implying that physical activity does not cause any changes [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical activity decreases the duration and intensity of fatigue [ 8 , 9 ], reduces anxiety and depression [ 10 ], increases muscle mass and strength, decreases disability in the upper extremities [ 11 ] and improves quality of life [ 12 , 13 ], as well as restoring and even improving functionality and well-being in women who have overcome breast cancer [ 14 ]. Several meta-analyses and reviews affirm that physical activity also contributes to reducing the risk of breast cancer recurrence [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], while others have obtained neutral results, implying that physical activity does not cause any changes [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this study followed the recommendations of the American College of Sports Medicine (ACSM), which state that cancer survivors should perform 150 min of moderate aerobic activity or 75 min of vigorous aerobic activity per week and resistance training two days per week [ 32 ]. Physical exercise plays an important role in improving quality of life [ 11 ] and preventing or delaying the onset of other diseases in cancer survivors [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] by improving aerobic capacity and muscle strength [ 11 ] and reducing fatigue [ 8 ], all of which are key elements in recovery from this disease and its sequelae [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests that well known breast cancer risk factors are associated with global DNA hypomethylation and increased epigenetic age [ 40 ], including lifestyle and dietary factors [ 41 , 42 ], body mass index [ 43 ], physical inactivity [ 44 ], and hormone exposure [ 45 ]. Furthermore, global DNA hypomethylation has been observed in cancers [ 46 ], including breast carcinomas, indicating that DNA methylation mediates gene-environment interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in body fat percentage were positively associated with LINE‐1 methylation values. In contrast to obesity, increased exercise was associated with a decreased risk of BC, and meta‐analyses have suggested that this may be due to a positive association between global CpG methylation and physical activity (Boyne et al, )…”
Section: Dietary Fat Obesity and Targeting Of Dna Methylation In Bcmentioning
confidence: 99%
“…Changes in body fat percentage were positively associated with LINE-1 methylation values. In contrast to obesity, increased exercise was associated with a decreased risk of BC, and meta-analyses have suggested that this may be due to a positive association between global CpG methylation and physical activity (Boyne et al, 2018) A methylation study of RARβ, E-cadherin 1 (ECAD) and P16 in (n = 803) breast tumour blocks from the Western New York Exposure and BC Study found that a greater WHR was associated with an increased probability (OR = 1.85) of hypermethylation of one or more of these genes (Tao et al, 2011). An analysis of non-malignant breast tissue from healthy women (n = 120) who had undergone cosmetic mammoplasty reported hypermethylation of ESR1 in obese women (BMI of ≥30 kgÁm −2 ) compared to both overweight (BMI of~25-29 kgÁm −2 ) and normal weight (BMI of <25 kgÁm −2 ; Daraei et al, 2017).…”
Section: Dietary Fat Obesity and Targeting Of Dna Methylation In Bcmentioning
confidence: 99%